Research on Advance Rate Effects and Their Regulation of Strata Pressure Behavior in Deeply Buried Weakly Cemented Longwall Panels Under High-Intensity Mining Conditions - Fenghai Yu; Baodeng Liu; Jin Yang (Applied Sciences)
This study investigates the exacerbated strata pressure manifestations induced by high-intensity mining in medium-deep weakly cemented coal seams in western China. An integrated research methodology combining theoretical analysis, field measurements, and numerical simulation was employed to develop a mechanical model of overburden fracture structures in weakly cemented mining faces, systematically revealing the dynamic effects of face advance rate on strata pressure behavior. The results demonstrate that the advance rate not only significantly governs the evolutionary patterns of roof caving and weighting intervals but also exhibits nonlinear correlations with the distribution characteristics of abutment pressure. Furthermore, microseismic parameters effectively characterize the response of strata pressure intensity to advance rate variations. The proposed dynamic control methodology provides both theoretical foundations for safe mining in weakly cemented strata and innovative technical solutions for ground control in deep high-intensity mining operations.